Plasma Power Density Produced by D-T Fusion Reaction - Majeed, Raad H.; Abed, Muayad M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Calculation of the power density of the nuclear fusion reactions plays an important role in the   construction of any power plants. It is clear that the power released by fusion reaction strongly depended on the fusion cross section and fusion reactivity. Our calculation concentrates on the most useful and famous fuels (Deuterium-tritium) since it represents the principle fuels in any large scale system like the so called tokomak.